Baropodometric technology used to analyze types of weight-bearing during hemiparetic upright position - Lidiane Teles de Menezes; Paulo Henrique Ferreira de Araujo Barbosa; Abraão Souza Costa; Anderson Castro Mundim; Gabrielly Craveiro Ramos; Clarissa Cardoso dos Santos Couto Paz; Emerson Fachin Martins (Fisioterapia em Movimento)
INTRODUCTION: Although baropodometric analysis has been published since the 1990s, only now it is found a considerable number of studies showing different uses in the rehabilitation. OBJECTIVE: To amplify the use of this technology, this research aimed to analyze baropodometric records during upright position of subjects with hemiparesis, describing a way to define weight-bearing profiles in this population. METHOD: 20 healthy subjects were matched by gender and age with 12 subjects with chronic spastic hemiparesis. This control group was formed to establish the limits of symmetry during weight-bearing distribution in the hemiparesis group. Next, hemiparesis group was submitted to procedures to measure baropodometric records used to provide variables related to the weight-bearing distribution, the arch index and the displacements in the center of pressure (CoP). Data were used to compare differences among kinds of weight-bearing distribution (symmetric, asymmetric toward non-paretic or paretic foot) and coordination system for CoP displacements. RESULTS: Hemiparesis group was compounded by eight symmetrics, eight asymmetrics toward non-paretic foot and four asymmetric toward paretic foot. Significant differences in the weight-bearing distributions between non-predominantly and predominantly used foot did not promote differences in the other baropodometric records (peak and mean of pressure, and support area). Mainly in the asymmetry toward non-paretic foot it was observed significant modifications of the baropodometric records. CONCLUSION: Baropodometric technology can be used to analyze weight-bearing distribution during upright position of subjects with hemiparesis, detecting different kinds of weight-bearing profiles useful to therapeutic programs and researches involving subjects with this disability.